Implementasi Kurikulum Merdeka dalam Pembelajaran Pendidikan Agama Islam di SMA Swasta Brigjend Katamso Medan - Siregar, Bahtiar; Abrianto, Danny; Syahrial, Abdi; Sitorus, Panca Abdi (LP2M STAI Darul Kamal NW Kembang Kerang NTB, 2024)
This study aims to analyze the implementation of the Merdeka Curriculum in Islamic Religious Education (PAI) learning at SMA Swasta Brigjend Katamso Medan. The Merdeka Curriculum is the latest policy from the Ministry of Education, Culture, Research, and Technology, designed to provide flexibility for educators in designing learning that is more adaptive to the needs of students. This research uses a qualitative approach with a case study method involving in-depth interviews with PAI teachers, direct observation of the learning process, and analysis of curriculum documents and lesson plans. The findings show that the implementation of the Merdeka Curriculum at SMA Swasta Brigjend Katamso Medan has been carried out effectively, although it still faces several challenges, such as limited resources and varying levels of understanding among the teachers. The Merdeka Curriculum allows PAI teachers to develop more interactive learning based on student needs, but further training and guidance for educators are required. The study also found that although the learning process is more flexible, periodic evaluation of the effectiveness of this new curriculum is still needed to optimize student competency achievement. In conclusion, while the implementation of the Merdeka Curriculum at SMA Swasta Brigjend Katamso Medan has been successful, there is a need to strengthen teachers' competencies and understanding in managing the curriculum for better optimization.